Wear and friction characterization of chlorella sp. microalgae oil based blended lubricant on pin on disc tribometer. (2020) - Thirugnanasambantham, R.; Elango, T.; Elangovan, K.
Abstract: In this particular research, friction as well as wear behavior for the working surfaces in contact had been carried out to examine their tendency during the use of an alternate lubrication into the mineral oil. The Chlorella sp. microalgae oil has a possible of a substitute for the mineral oil 5W-30 as well as they may be generally obtainable in considerable quantity. The test had been carried out on a pin on disc tribometer using various conditions. The modified Chlorella sp. microalgae oil combined with the mineral oil in various ratios for additional testing. According to the research carried out 10% and 20% concentration for the altered bio-oil revealed an important enhancement in terms of lowering wear rate coefficient of friction mean wear scar diameter as well as better the worn surface morphology with compare to the 5W-30 mineral oil. The optimum rise within the response parameters had been acquired with relative for their tribological analysis when the concentration for the modified Chlorella sp. algae oil improves beyond 15% and reaches 20%. Effectively, the performance of (5W-30) A10, (5W-30) A15 and (5W-30) A20 samples has a significantly better possible effect throughout the tribological analysis being a lubricant with regards to the ecological issue as well as eco-friendly.